Evaluation of porcine GM-CSF during PRRSV infection in vitro and in vivo indicating a protective role of GM-CSF related with M1 biased activation in alveolar macrophage during PRRSV infection - Ji, Qi; Qu, Guanggang; Liu, Bing; Bai, Yang; Wang, Guihua; Chen, Rui; Zheng, Xu; Zhang, Zhigang; Yang, Yonglin; Wu, Chunyan (Frontiers in Immunology, 2022)
Granulocyte-macrophage colony stimulating factor (GM-CSF), participates in diverse biological processes associated with innate and adaptive immunity, has unknown effects during PRRSV infection. Here, a double-antibody sandwich ELISA for pGM-CSF was developed in-house for evaluation of pGM-CSF level during PRRSV infection both in vitro and in vivo. In in vitro assay, it was notable that PRRSV-infected porcine alveolar macrophages (PAMs) yielded inconsistent pGM-CSF protein- and mRNA-level, suggesting a post-transcriptional inhibition of pGM-CSF mRNA was employed by PRRSV. Meanwhile, concurrent analysis of pGM-CSF levels in serum samples from PRRSV-infected piglets suggested that effect of PRRSV infection demonstrated minimum effect on pGM-CSF levels regardless of PRRSV virulence phenotypes. Moreover, in vitro treatment of PAMs with pGM-CSF prior PRRSV inoculation did not inhibit PRRSV replication in PAMs although genes downstream of pGM-CSF in PAMs could be upregulated by pGM-CSF treatment. Meanwhile, knockdown of pGM-CSF using siRNA did not enhance PRRSV replication as well. Intriguingly, therapeutic antibody treatment of HP-PRRSV-infected piglets led to significantly increased serum pGM-CSF levels, thus aligning with low pneumonia incidence and low intracellular PRRSV-RNA levels in PAMs of therapeutic antibody treated piglets. Furthermore, transcriptome analysis of PAMs from infected piglets revealed increased serum pGM-CSF levels correlated with activation of downstream signal of pGM-CSF in PAMs as evidenced by a M1-like phenotypes of gene expression pattern, implying a potential host-protective role played by pGM-CSF for PRRSV infection in vivo. In conclusion, our results demonstrated developments of a highly sensitive and specific ELISA for pGM-CSF and revealed a potential protective role conferred by pGM-CSF during PRRSV infection.